2021
DOI: 10.26656/fr.2017.5(3).534
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic of antimicrobial activities of lactic acid bacteria in fermented Tilapia nicoliticus incorporated with selected spices

Abstract: Fermented tilapia (Tilapia nicoliticus) is one of the famous fermented food in Malaysia. Lactic acid bacteria (LAB) which well known as GRAS (Generally Regarded as Safe) are present in most fermented foods and they are well-known non-pathogenic bacteria that play an important role in everyday life. Apart from LAB, spices have also been used for centuries across different regions of the world to improve aroma, flavour and food preservative. This research was aimed to explore a potential natural food preservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Maman pickle, a lactic acidproducing pickled vegetable, offers a distinct flavour [9]. Another traditional food, fermented fish, is made by preserving fish through fermentation, typically combined with salt, herbs, spices, and vegetables to enhance flavour and texture during the process [10]. Tempoyak, a traditional Southeast Asian fermented durian flesh, is popular in Indonesia and Malaysia, often used as a seasoning or ingredient in various dishes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Maman pickle, a lactic acidproducing pickled vegetable, offers a distinct flavour [9]. Another traditional food, fermented fish, is made by preserving fish through fermentation, typically combined with salt, herbs, spices, and vegetables to enhance flavour and texture during the process [10]. Tempoyak, a traditional Southeast Asian fermented durian flesh, is popular in Indonesia and Malaysia, often used as a seasoning or ingredient in various dishes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown that water extract of P. edule seed can inhibit the growth of Aspergillus flavus (Listyorini et al, 2021). According to Ismail et al (2021) lactic acid bacteria that isolated from fish fermented Tilapia nicolicus incorporated with spices such chili, turmeric and black pepper have antimicrobial activity against B. cereus, S. aureus, E. coli and Salmonella enterica serovar Thyphimurium.…”
Section: Introductionmentioning
confidence: 99%
“…Salt preserves fresh fish by lowering the rate of humidity to the level at which bacteria and enzyme activity are inhibited. Not only that, but chloride ions are also toxic to some microorganisms (Mustafa, 2019), and LAB were successfully isolated from fermented fish (Zakaria et al, 2018;Ismail et al, 2021). LAB are considered to be a major group of probiotic bacteria and it is believed that these major group of bacteria can assist in keeping the balance between harmful and beneficial bacteria in the stomach consequently maintaining the digestive system (Hugo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%